2019
DOI: 10.1111/os.12439
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Jintiange Capsules in the Treatment of Osteoporosis: A Network Meta‐analysis

Abstract: Objective To evaluate the efficacy of Jintiange capsules and Jintiange combined with other therapies in the treatment of osteoporosis. Methods A systematic review of the literature was conducted through databases including China National Knowledge Infrastructure (CNKI), the VIP Database for Chinese Technical Periodicals (VIP), Wanfang, and PubMed from inception to April 2018. Network meta‐analysis was used to determine the relative efficacy of related treatments on osteoporosis. The primary outcome measures ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 3 publications
2
22
0
Order By: Relevance
“…Jtg, a traditional medicine composed of various animal bones and organic compounds such as collagen and polysaccharides, has demonstrated outstanding efficacy in treating osteoporosis in various animal and clinical trials and is recommended for the treatment of osteoporosis in China. In addition, increasing evidence suggests that Jtg therapies may reduce bone loss and accelerate bone formation ( Sun et al, 2019 ; Zhao et al, 2019 ; Zhao et al, 2021 ). When we combined this with the basic findings of several previous studies, we hypothesized that Jtg might also play a critical role in the treatment of another chronic orthopedic disease, OA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jtg, a traditional medicine composed of various animal bones and organic compounds such as collagen and polysaccharides, has demonstrated outstanding efficacy in treating osteoporosis in various animal and clinical trials and is recommended for the treatment of osteoporosis in China. In addition, increasing evidence suggests that Jtg therapies may reduce bone loss and accelerate bone formation ( Sun et al, 2019 ; Zhao et al, 2019 ; Zhao et al, 2021 ). When we combined this with the basic findings of several previous studies, we hypothesized that Jtg might also play a critical role in the treatment of another chronic orthopedic disease, OA.…”
Section: Discussionmentioning
confidence: 99%
“…Artificial tiger bone powder, also called Jintiange (Jtg) capsules, is mixed in a pre-determined ratio with calcium, collagen, bone morphogenetic protein, bone growth factors, polypeptides, amino acids, and polysaccharides and used to treat bone-related conditions. Jtg is known for having similar medical effects to real tiger bone and has been reported to have distinct effects on osteoporosis in many experimental animal and clinical studies ( Sun et al, 2019 ). However, the effects of Jtg on articular cartilage and subchondral bone and its underlying mechanisms remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional herbal medicine has been used as a complementary and alternative treatment option for patients with osteoarthritis for a long time. JTG capsule may improve the function of the knee joint to a certain extent and has a particular analgesic effect [ 35 ]. However, its efficacy and side effects in treating knee osteoarthritis are uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…18 Jintiange capsule (JTG) is a formula approved by the Chinese Food and Drug Administration (CFDA) as a TB substitute, which is composed of bionic TB powder with similar ingredients to the natural TB, and rich in bioactive peptides, proteins, amino acids and minerals. 19 That bionic TB powder is prepared from the skeletons of several farmed edible animals including pigs, goats and deer. 19 Ample experimental studies and large clinical trials have demonstrated the prominent efficacies of JTG on alleviating osteoporosis in patients, [19][20][21][22][23] improving the bone microstructure, strengthening the bone biomechanical property in ovariectomized rats, 24 and curing patients with aromatase inhibitor-associated musculoskeletal symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…19 That bionic TB powder is prepared from the skeletons of several farmed edible animals including pigs, goats and deer. 19 Ample experimental studies and large clinical trials have demonstrated the prominent efficacies of JTG on alleviating osteoporosis in patients, [19][20][21][22][23] improving the bone microstructure, strengthening the bone biomechanical property in ovariectomized rats, 24 and curing patients with aromatase inhibitor-associated musculoskeletal symptoms. 25 Hence JTG has taken place of TB to treat osteoporosis in clinical for years, 26,27 and been listed as an effective treatment in the guidelines for the treatment of osteoporotic fractures since 2017.…”
Section: Introductionmentioning
confidence: 99%